2021
DOI: 10.3390/ani11051442
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural Holdings and Slaughterhouses’ Impact on Patterns of Pathological Findings Observed during Post-Mortem Meat Inspection

Abstract: Meat inspection data can provide valuable information about herd health to producers, veterinarians and veterinary authorities and can be used as a feedback system for farmers to improve their herd management. The aim of this study was to analyse the influence of agricultural holdings, slaughterhouses and time periods (quarters) on the occurrence and composition of the prevalence of post-mortem findings of 4 million pigs slaughtered in Austria in 2016, by applying a permutation multivariate analysis of varianc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 40 publications
(86 reference statements)
0
10
0
Order By: Relevance
“…With a large dataset (n=592,268) of Dutch slaughter cows, the association of post-mortem health observations with carcass weight and trimming loss (exceeding 5 kg) were determined. In our model, random herd effect explained around 20 percent of total variation in carcass weight, which is less compared to Klinger et al. (2021) .…”
Section: Discussionmentioning
confidence: 61%
“…With a large dataset (n=592,268) of Dutch slaughter cows, the association of post-mortem health observations with carcass weight and trimming loss (exceeding 5 kg) were determined. In our model, random herd effect explained around 20 percent of total variation in carcass weight, which is less compared to Klinger et al. (2021) .…”
Section: Discussionmentioning
confidence: 61%
“…Impact analysis of the simulation models for the two strategies revealed that a higher prevalence of lung lesions if not adopting one of the strategies was the main factor determining the net benefit change on-farm. With the increasing prevalence of lung lesions (10), adopting an effective strategy to decrease respiratory infections will become more relevant and more economically beneficial. The results presented here can be used to support pig producers in choosing cost-effective management strategies to reduce the prevalence of lung lesions at slaughter by improving animal health and welfare.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of pleurisy and pneumonia at slaughter has increased globally in the past two decades (10) and the high prevalence of lung lesions and associated negative impacts on farm economics are a known issue (11). Since the prevalence of lung lesions in pigs depends on both infectious agents and environmental factors [e.g., air quality, production system, flooring type, number of pigs per pen and direct contact (nose-to-nose) between infected and susceptible pigs (11)], strategies to improve animal health, working environment and farm finances need to be implemented.…”
Section: Introductionmentioning
confidence: 99%
“…Alban et al (2022) detected differences in the number of available codes, code terminology, and frequency of meat inspection findings in European countries. Klinger et al (2021) showed differences between and within slaughterhouses on the observed prevalence of meat inspection findings. Within a slaughterhouse, differences between meat inspection decisions of detained carcasses were observed between meat inspection personnel (Arzoomand et al 2019).…”
Section: Introductionmentioning
confidence: 93%
“…For example, the prevalence of various diseases in different countries affects which palpations and incisions are needed in each country. Recent studies have shown systemic variations in meat inspection between countries (Alban et al 2022), within countries (Klinger et al 2021) and at individual inspector level within a slaughterhouse (Arzoomand et al 2019). Alban et al (2022) detected differences in the number of available codes, code terminology, and frequency of meat inspection findings in European countries.…”
Section: Introductionmentioning
confidence: 99%